Impact of Storage Conditions on a New Child-Friendly Dispersible Tablet for Treating Tuberculosis in Pediatrics - Javier Suárez González; Ana Santoveña Estévez; Mabel Soriano; Jose Bruno Fariña (Pharmaceutical Sciences, 2022)
Background: In 2020 the composition and procedure to elaborate a new formulation containing Isoniazid, Pyrazinamide and Rifampicin to treat tuberculosis in pediatric patients was published. The temperature and relative humidity in Tuberculosis-endemic countries are high, > 30 ºC and > 70% respectively and thus these meteorological conditions required a new dosage form. The objective of this work is to register changes in tablet quality and stability over time when exposed to different storage conditions according to ICH. Methods: Tablets were subjected to accelerated, long term and low relative humidity conditions. The effect of light was also tested. Quality was measured by evaluating weight changes tensile strength, disintegration time, and drug content. Hydrazine formation was also evaluated as it is considered a mutagenic degradation product. Results: Tablets stored at low relative humidity showed the best stability. There was no statistically significant difference between tablets exposed to or protected from light. Moreover, the formation of Hydrazine was not detected during stability studies. Conclusion: This new dosage form for treating Tuberculosis is stable and able to maintain its quality when appropriate storage conditions are used.